DETERMINATION OF THE LONGITUDINAL DISTANCE BETWEEN FURROWS OF MODULAR PLOUGH AGGREGATED WITH HIGH-POWER TRACTORS - A. N. Khudoyarov; R. Yu. Makhmudov; M. A. Yuldasheva; B. A. Kadirov, U. Abdullaeva (Scholars Digest Publishing, 2023)
The article presents the results of the research on determining the longitudinal distance between the modular plough furrows that are aggregated with high-power tractors. In addition to two-tier ploughs, modular ploughs for general purposes are widely used in our Republic, but these ploughs are imported from foreign countries, and it has been determined that they do not fully meet the requirements for plowing land in the conditions of our Republic. Based on this, modular ploughs designed for general work have been developed for high-powered wheeled tractors widely used in our country. According to the results of the research, the longitudinal distance between plug furrows intended for general work is less than 88 cm. has been determined.
Keywords: High-power tractor, aggregate, modular plough, furrow, longitudinal distance, research, result, double-layer plough, plough, resource-efficient, technology, structural scheme, plough-turning surface